Study on the Effect of Performance Mediation on the Relationship between Work Discipline, Motivation and Compensation on Teacher Quality in Junior High School (SMP) in Kongbeng District - Majuliyati, Majuliyati; Rachman, Marjoni; Latif, Imam Nazarudin (IJEBD (International Journal of Entrepreneurship and Business Development), 2025)
Purpose: The purpose of this study is to analyze the influence of work discipline, work motivation, and compensation on teacher performance, as well as their influence on the quality of teacher performance both directly and through the mediation variables of teacher performance in junior high schools (SMP) in Kongbeng District Design/methodology/approach: This study uses a quantitative approach with a survey method. The sample consisted of 76 junior high school teachers in Kongbeng District who were selected using the purposive sampling technique. Data was collected through a questionnaire that had been validated and analyzed using Structural Equation Modeling (SEM) with the help of SmartPLS software to test the influence of work discipline, motivation, and compensation on teacher quality through performance as a mediating variable. Findings: The results of the study show that work discipline, motivation, and compensation have a positive and significant effect on teacher performance. Teacher performance also has a positive effect on teacher quality, and significantly mediates the relationship between work discipline, motivation, and compensation and teacher quality. Research limitations/implications: the use of cross-sectional designs that only describe momentary conditions, the use of self-report questionnaires that have the potential to cause perception bias, and the use of external factors such as leadership, facilities, and organizational culture that may also affect teacher performance and quality. Practical implications: These findings confirm that improving teacher quality can be achieved not only through direct factors such as motivation and compensation, but also through improved teacher performance. The practical implication is the importance of the role of school management in strengthening work discipline, providing appropriate motivation, and proper compensation to support the overall improvement of teacher performance and quality. Paper type: Research paper